(untitled) (CIPEEX, 2024)
THIS PAPER ADDRESSES THE DEVELOPMENT OF THE EMPREGAI PLATFORM, A MOBILE APPLICATION DESIGNED TO FACILITATE THE HIRING AND PROVISION OF GENERAL SERVICES, CONNECTING SERVICE PROVIDERS AND CLIENTS. WITH THE INCREASED USE OF SMARTPHONES, DRIVEN BY THE COVID-19 PANDEMIC, MANY SERVICES HAVE HAD TO ADAPT TO THIS NEW REALITY. IN THIS CONTEXT, THERE IS A GROWING DEMAND FOR QUALIFIED AND WELL-REVIEWED PROFESSIONALS. THE EMPREGAI PLATFORM EMERGES AS A SOLUTION BY OFFERING AN INTUITIVE AND EFFICIENT INTERFACE, ALLOWING WORKERS TO FIND JOB OPPORTUNITIES IN THEIR RESPECTIVE FIELDS OF EXPERTISE AND ENABLING CLIENTS TO FIND QUALIFIED PROFESSIONALS FOR VARIOUS TYPES OF SERVICES. THROUGH THE MOBILE APPLICATION, USERS CAN CREATE PROFILES, PROVIDE INFORMATION ABOUT THEIR SKILLS AND EXPERIENCES, AS WELL AS LIST THE SERVICES THEY ARE WILLING TO OFFER. WITH ADVANCED SEARCH AND FILTERING FEATURES, CLIENTS CAN FIND PROFESSIONALS SUITABLE FOR THEIR SPECIFIC NEEDS, TAKING INTO CONSIDERATION RATINGS AND COMMENTS FROM OTHER USERS. ADDITIONALLY, THE APPLICATION ALLOWS FOR SCHEDULING AND DIRECT COMMUNICATION BETWEEN SERVICE PROVIDERS AND CLIENTS, MAKING THE HIRING PROCESS MORE EFFICIENT AND CONVENIENT FOR BOTH PARTIES. BY PROMOTING DIRECT CONNECTIONS BETWEEN WORKERS AND CLIENTS, THE EMPREGAI PLATFORM AIMS TO STREAMLINE THE HIRING PROCESS FOR GENERAL SERVICES, ELIMINATING INTERMEDIARIES AND REDUCING COSTS. FURTHERMORE, IT AIMS TO PROVIDE A SAFE AND RELIABLE ENVIRONMENT WHERE USERS CAN FIND QUALIFIED AND TRUSTWORTHY PROFESSIONALS TO MEET THEIR NEEDS.